High yielding dairy cattle husbandry and their production performance at Baghabari Milk Vita areas of Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
The aim of this study was to identify the recent husbandry practices of high yielding dairy cows including their production performances surrounding the Baghabari Milk Vita areas of Bangladesh. The survey was conducted on 15 households of Pabna (Santhia) and Sirajgonj (Shahjadpur) districts. Data were also collected from six bathans at Sahajadpur of Sirajgonj district. Medium scale farming (67%) observed more compared to small (27%) and large (7%) in the studied areas with maximum 20 milch cows. Highest average milk production recorded 213 liters per day in few households and the milk price varied between 31 to 35 BDT per liter.  Most of the farmers (80%) used the semen of Milk Vita because of its excellence (73%) for better productivity in their progenies. About 73% farmers directly depended on Milk Vita for selling their cows’ milk while 27% on contract persons (Ghos). Two feeding systems were available in the surveyed areas based on the availability of greed grass/fodder: stall feeding (July to November) and bathan feeding (December to June). Total number of AI services (1.62) differed according to crossbreeds (P< 0.05) and rearing system (P< 0.01) with peak milk production 17.57 liters per day. Breeding of the high yielding cows was conducted through artificial insemination (80%) and mainly by the free semen of Milk Vita (80%). Hybrid fodder production, ensuring quality feed/ingredients and milk price, and recorded breeding based on predominant breed could strengthen the overall dairying at Baghabari Milk Vita regions of Bangladesh.Asian Australas. J. Biosci. Biotechnol. 2017, 2 (1), 60-67